Training on the Utilization of Green Grass Jelly For Food and Beverage Ingredients: Participatory Training-Based Intervention - Sutiharni Sutiharni; Dewi Handayani; Indriyani Indriyani; Najirah Umar; Mulono Apriyanto; Citra Indriyati; Bestfy Anitasar; Siti Rahmah Hidayatullah Lubis; Lukman Handoko (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aimed to empower local communities by enhancing their knowledge and skills in utilizing green grass jelly (Cyclea barbata Miers) as an alternative ingredient for healthy food and beverage products. Conducted over three days, the training involved 12 participants with diverse backgrounds, including homemakers, youth, and micro-entrepreneurs. The program adopted a participatory training approach that combined theoretical knowledge with hands-on practice, including plant identification, jelly extraction techniques, hygiene practices, and product innovation. Pre- and post-training assessments revealed significant improvement in participants’ understanding and abilities. Initially, only 25% of participants were familiar with the plant's benefits and usage. After the training, 100% of participants demonstrated comprehension of the nutritional value and processing methods, and 75% successfully created product variants such as fruit-infused jelly drinks and herbal puddings. The training encouraged creativity and showed the potential of green grass jelly as a sustainable, low-cost, and health-promoting ingredient suitable for micro-entrepreneurial ventures. The program concluded that community-based food innovation training can serve as an effective model for promoting local resources, enhancing food security, and developing rural economies. It also emphasized the importance of combining traditional knowledge with modern food processing techniques to generate added value and marketable products.